The impact of bars and interactions on optically selected AGNs in spiral galaxies - Alonso Giraldes, Maria Sol (2018)
Aims. With the aim of performing a suitable comparison of the internal process of galactic bars with respect to the external effect of interactions on driving gas toward the inner most region of the galaxies, we explored and compared the efficiency of both mechanisms on central nuclear activity in optically selected active galactic nuclei (AGNs) in spiral galaxies. Methods. We selected homogeneous samples of barred AGNs and active objects residing in pair systems, derived from the Sloan Digital Sky Survey (SDSS). In order to carry out a reliable comparison of both samples (AGNs in barred hosts in isolation and in galaxy pairs), we selected spiral AGN galaxies with similar distributions of redshift, magnitude, stellar mass, color and stellar age population from both catalogs. With the goal of providing an appropriate quantification of the influence of strong bars and interactions on nuclear activity, we also constructed a suitable control sample of unbarred spiral AGNs without a companion and with similar host properties to the other two samples. Results. We found that barred optically selected AGNs show an excess of nuclear activity (as derived from the Lum[OIII]) and accretion rate onto a central black hole () with respect to AGNs in pairs. In addition, both samples show an excess of high values of Lum[OIII] and with respect to unbarred AGNs in the control sample. We also found that the fractions of AGNs with powerful nuclear activity and high accretion rates increase toward more massive hosts with bluer colors and younger stellar populations. Moreover, AGNs with bars exhibit a higher fraction of galaxies with powerful Lum[OIII] and efficient with respect to AGN galaxies inhabiting pair systems, in bins of different galaxy properties. Regarding AGNs belonging to pair systems, we found that the central nuclear activity is remarkably dependent on the galaxy pair companion features. The Lum[OIII] for AGNs in pairs is clearly enhanced when the galaxy companion exhibits a bright and more massive host with high metallicity, blue color, efficient star formation activity and young stellar population. The results of this work reveal an important capacity of both mechanisms, bars and interactions, to transport material towards the galaxy central regions. In this context, it should also be noted that the internal process of the bar is more efficient at improving the central nuclear activity in AGN objects than that corresponding to the external mechanism of the galaxy-galaxy interactions.